2020
DOI: 10.29309/tpmj/2020.27.05.4317
|View full text |Cite
|
Sign up to set email alerts
|

Learning strategies used by dental students and dentists using the ark questionnaire.

Abstract: Objectives: To determine the preferred learning styles of Dental students and Dentists among various dental colleges using the VARK questionnaire. Study Design: Cross-sectional study. Setting: Various Dental Colleges in Karachi & Rawalpindi using the VARK questionnaire. Period: From June 2018 to February 2019. Material & Methods: Students, house-officers and demonstrators of dental medical college and hospital were asked to fill the VARK questionnaire which consists of 16 items. Four modes of learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
0
1
Order By: Relevance
“…Furthermore, the multimodal mode represents only 1.5%. 31 Also, the study results differed from two studies that were performed among Egyptian nursing students. The first study involved 641 students from the Faculty of Nursing, Assiut University, and concluded that the highest percentage of students preferred the unimodal learning styles (kinesthetic/tactile learning style, followed by visual learning style and then auditory learning style).…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, the multimodal mode represents only 1.5%. 31 Also, the study results differed from two studies that were performed among Egyptian nursing students. The first study involved 641 students from the Faculty of Nursing, Assiut University, and concluded that the highest percentage of students preferred the unimodal learning styles (kinesthetic/tactile learning style, followed by visual learning style and then auditory learning style).…”
Section: Discussioncontrasting
confidence: 57%
“…Respondents were allowed to choose two or more options according to their preference." 11 The research team decoded each student's responses to the VARK questionnaire to assess their preferred learning style and modes using the link (https://vark-learn.com/the-varkquestionnaire/). 12 The results were mailed back to the students so that they could use the "VARK help sheets" to improve The most preferred learning combination was VARK which was chosen by 35.1 % of the students followed by VR as the least preferred learning style combination as it was only chosen by 2 students out of 271 as shown Table 2 Upon assessing the association between the sociodemographic profile of the medical students and their preferred learning styles, a significant difference was observed only in learning stylesadopted by students in the pre-clinical and clinical yearsof medical school (p=0.01), as shown in Table 3.…”
Section: Methodsmentioning
confidence: 99%